2017
DOI: 10.1080/01616412.2017.1348680
|View full text |Cite
|
Sign up to set email alerts
|

A novel biomimetic composite substitute of PLLA/gelatin nanofiber membrane for dura repairing

Abstract: In conclusion, the new biomimetic composite substitute provides alternative substitute for dura repairing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
1
24
0
1
Order By: Relevance
“…This bionic and porous scaffold provides holes or cracks, which is beneficial to the migration of patient's autologous cells. The migration of cells is important for the degradation of implanted materials and the reconstruction of the dura mater [38]. In addition, by changing the composition and concentration of each polymer, the toughness of the fibers can be adjusted, and the appropriate level of mechanical strength of the synthetic dural substitute can be obtained [39].…”
Section: Macromolecular Polymer Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This bionic and porous scaffold provides holes or cracks, which is beneficial to the migration of patient's autologous cells. The migration of cells is important for the degradation of implanted materials and the reconstruction of the dura mater [38]. In addition, by changing the composition and concentration of each polymer, the toughness of the fibers can be adjusted, and the appropriate level of mechanical strength of the synthetic dural substitute can be obtained [39].…”
Section: Macromolecular Polymer Materialsmentioning
confidence: 99%
“…Some researchers have attempted to prepare dural substitutes by adding gelatin or silk fibroin into the polymer. This method not only ensures the bionic structure of the dural substitute but also increases the biological function and improves the surface properties of the material, thereby enhancing its repair effects [38].…”
Section: Macromolecular Polymer Materialsmentioning
confidence: 99%
“…Методологія оцінки замінника ТМО передбачає: характеристику фізичних властивостей (міцність на розтягнення, спроможність швів, кут змочування (контактний кут), ζ-потенціал), цитологічних (клітинна культура, тест на цитотоксичність (МТТ-тест), конфокальна лазерна сканувальна мікроскопія, сканувальна електронна мікроскопія) і вивчення біосумісності (проведення експерименту з макро-та мікроскопічною (гістологічною) оцінкою за спеціальними методиками (забарвлення трихромом за Массоном) [35]. Характеристику репаративних процесів визначають гістологічними та мікроскопічними методами.…”
Section: теоретическое обоснование эффективности применения биополимеunclassified
“…The electrospun nanofibers of polymer materials have good properties, such as porosity, water retention, tissue compatibility, and mechanical properties, and are, therefore, favored in the field of tissue repair, including skin, dura mater, muscle, bone, and cartilage (Su and Wang, 2015 ; Paschoalin et al, 2017 ; Zarei and Soleimaninejad, 2018 ). It has been reported that electrospun nanofibers of PLA/gelatin blends are one of the most ideal material combinations for soft tissue repair applications (Liu et al, 2014 ; Xu et al, 2015 , 2017 ; Deng et al, 2017 ). It has been reported in the literature for the repair of brain dura mater, which can promote the migration and colonization of cells and achieve tissue regeneration (Deng et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that electrospun nanofibers of PLA/gelatin blends are one of the most ideal material combinations for soft tissue repair applications (Liu et al, 2014 ; Xu et al, 2015 , 2017 ; Deng et al, 2017 ). It has been reported in the literature for the repair of brain dura mater, which can promote the migration and colonization of cells and achieve tissue regeneration (Deng et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%